ANALYSIS OF POVERTY STRUCTURE IN INDONESIA USING A MULTIFACTORIAL APPROACH - Pardita, Dewa Putu Yudi; Arjawa, I Gde Wedana; Paramita, Anak Agung Gde Krisna; Setena, I Made (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Poverty is a crucial issue that affects various social and economic aspects in Indonesia, requiring severe attention to achieve sustainable development. This study aims to analyse the impact of economic growth, income distribution, human development index (HDI), government social assistance, and consumption on poverty levels in Indonesia. Using a quantitative research approach with secondary data from Statistics Indonesia for 2019-2023, this study employs panel data regression analysis using EViews 13 to examine the relationship between variables. The findings indicate that economic growth, income distribution, and HDI significantly impact poverty reduction, while government social assistance and consumption do not show a significant influence. These findings imply the need for inclusive economic growth, fairer income distribution, and investments in human capital development. Moreover, there is a need to improve the design of social assistance programs and strategies to promote productive consumption to be more effective in reducing poverty. This highlights the importance of targeted and integrated policies to address poverty in Indonesia comprehensively.JEL: I32, O15, H53.